Marketing Analysis and Availability of Drugs with ATC Code N07BB: Current Trends - Shapovalov, Valentyn; Derkach, Anatolii (SSP Modern Pharmacy and Medicine, 2024)
Marketing analysis was conducted and the availability of drugs for the treatment of alcohol addiction under the ATX code N07BB was assessed. The study covers three main clinical and pharmacological groups: Disulfiram (N07BB01), Naltrexone (N07BB04) and other drugs (N07BB10). The features of the release forms (tablets, granules, powders), availability and release regimens were analyzed. Disulfiram and Naltrexone drugs are available by prescription, while combined drugs are available without a prescription. The data obtained indicate a high potential for the use of these drugs for individualized and affordable therapy of alcohol addiction. A thorough marketing assessment was undertaken to evaluate the availability of medications under ATX code N07BB, focusing on their role in alcohol addiction treatment. The analysis covered three principal clinical and pharmacological categories: Disulfiram (N07BB01), Naltrexone (N07BB04), and an additional subgroup of products (N07BB10). Researchers examined various dosage forms – including tablets, granules, and powders – alongside their accessibility and distribution requirements. Disulfiram and Naltrexone both require a physician’s authorization, while certain combination therapies can be purchased without a prescription. Based on these data, there is clear evidence of a robust potential for these therapies to be used in personalized and cost-effective interventions for alcohol dependence. Moreover, their availability in multiple formats caters to patients’ individual preferences and clinical needs, potentially enhancing adherence and treatment success. By offering a wide variety of administration possibilities, these medications are poised to improve outcomes in different healthcare settings. Research into dosing schedules and side effects can guide clinicians in refining therapeutic approaches. Healthcare professionals may consider these agents as part of a strategy, incorporating psychosocial support and other interventions that address the nature of alcohol dependence.